Building Community Resilience to Climate Change in Jakarta: A Public Health Approach Integrating Policy, Practice, and Education - Jonah Abraham; Andi Fatihah Syahrir; Neva Dian Permana; Matilda Munoz; Sarah Armalia (Community Medicine and Education Journal, 2025)
Climate change poses significant and escalating threats to public health in Jakarta, Indonesia, including increased risks of vector-borne diseases, heat-related illnesses, and mental health impacts exacerbated by flooding and displacement. This study examined the current state of community resilience to these climate-related health threats and evaluated the effectiveness of existing policies and educational interventions. A mixed-methods approach was employed, combining a cross-sectional survey of Jakarta residents (n= 850), semi-structured interviews with key stakeholders (n= 25) from government agencies, NGOs, and community organizations, and a policy review of relevant Indonesian and Jakarta-specific regulations and strategic plans. The survey assessed climate change awareness, perceived health risks, adaptive capacity, and access to resources. Interviews explored policy implementation challenges, inter-sectoral collaboration, and community engagement strategies. The policy review analyzed alignment with international best practices and identified gaps. The survey revealed moderate levels of climate change awareness but significant gaps in understanding of specific health risks (62% aware of general climate change, but only 38% aware of the link to dengue fever increase). Perceived adaptive capacity was low, particularly among vulnerable populations (low-income households, those living in flood-prone areas). 75% of respondents in flood-prone areas reported lacking adequate resources to cope with flooding events. Interviews highlighted challenges in inter-sectoral coordination, limited funding for community-based programs, and a lack of culturally appropriate health education materials. The policy review found that while national-level policies exist, Jakarta-specific implementation lags, particularly in integrating health considerations into urban planning and disaster preparedness. In conclusion, building community resilience to climate change in Jakarta requires a multi-pronged approach. This includes strengthening health system preparedness, developing targeted and culturally appropriate health education programs, improving inter-sectoral collaboration, enhancing community engagement, and integrating health considerations into all relevant policies. Specific recommendations include strengthening early warning systems for heat waves and floods, expanding access to clean water and sanitation, promoting climate-resilient housing, and investing in community-based adaptation projects.